Transformasi Kompetensi Guru melalui Pemanfaatan AI dalam Penulisan Artikel Jurnal - R. Elfrida Panjaitan; Lasminar Lusia Sihombing; Roy Sahputra Saragih; Jesika Melina Simamora; Juliana Rotua Pasaribu; Jenny Gultom; Renovand Mikael Situmorang (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
This community service aims to improve teachers' competence in utilizing artificial intelligence (AI) as a support for writing scientific journal articles. This activity was carried out at the UPTD SD Negeri 121246, Jalan Bahkora Dua Atas, Siantar Simarimbun District, Pematangsiantar City, with a total of 10 teachers. The method of implementing activities is carried out through discussions, literature studies, material delivery, and direct practice of using AI in literature search, problem mapping or gap analysis, preparation of draft scientific articles, and determination of publication journal targets. The results showed that 90% of teachers understood the material presented, especially related to the use of AI to speed up the reference search process, systematically compile articles, get to know academic AI devices other than ChatGPT, and understand the ethical limits of using AI to avoid plagiarism and ethical violations of scientific publications. This activity has a positive impact on improving teacher professionalism, especially in producing scientific papers that are relevant, structured, and have the potential to support career development and credit scores for teachers' functional positions.